Modafinil’s effects on cognition and sleep quality in affectively-stable patients with bipolar disorder: a pilot study - Lipschitz, Jessica M.; Perez-Rodriguez, Mercedes; Majd, Marzieh; Larsen, Emmett; Locascio, Joseph; Pike, Chelsea K.; Shanahan, Megan; Burdick, Katherine E. (Frontiers in Psychiatry, 2023)
Introduction: Despite advances in the treatment of bipolar disorder (BD), most patients do not achieve complete inter-episode recovery and functional disability is common. During periods of relative remission, many patients continue to experience neurocognitive dysfunction, reduced daytime activity levels, and sleep disturbances. This 8-week, randomized, placebo-controlled pilot study evaluated the feasibility, safety and preliminarily efficacy of the wake-promoting drug, modafinil (Provigil®), on neurocognitive functioning, daytime sleepiness, and sleep quality in affectively stable BD patients. Methods: Twelve individuals with affectively stable BD were recruited and randomized to a flexible dose of modafinil (100 to 200 mg/day) or placebo, adjunctive to a therapeutic dose of a mood stabilizer. Weekly in-person visits tracked sleep quality and daytime sleepiness as well as side effects and mood symptoms. Neurocognitive functioning was assessed at baseline, week 4, and week 8. Results: No serious adverse events were reported. Newly emergent side effects in the modafinil group included heart palpitations, itching, fatigue, and decreased energy. Two patients discontinued modafinil owing to side effects and one of these patients withdrew from the study. One patient discontinued placebo and was withdrawn from the study. Preliminary evaluations of clinical efficacy showed a marginally significant interaction between treatment group and time in two cognitive domains (speed of processing and verbal learning), indicating greater improvement in the modafinil group versus placebo. Additionally, there was a marginally significant effect of treatment group on daytime sleepiness, suggesting lower daytime sleepiness in the modafinil group versus placebo. Counterintuitively, we found a significant treatment group by time interaction effect on sleep quality, suggesting greater improvement in sleep quality in the placebo group versus the modafinil group. Discussion: Results suggest that modafinil is a relatively safe medication for affectively stable BD patients when given with adjunctive mood stabilizers. Results are suggestive of cognitive benefit and improved daytime sleepiness, but worse sleep quality in those patients prescribed modafinil. A fully powered clinical trial is warranted with specific attention to the characteristics of patients who are most likely to benefit from treatment with modafinil and other methodological lessons learned from this pilot.